Pengaruh Struktur Modal, Likuiditas, Ukuran Perusahaan, dan Umur Perusahaan Terhadap Kinerja Keuangan pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022 - Darma Riswan; Lidya Martha (Trending: Jurnal Manajemen dan Ekonomi, 2024)
This research aims to examine the influence of capital structure, liquidity, company size, and company age variables on financial performance in manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2022. The data used in this research are secondary data. The population in this study consists of 245 companies, and the sample selection procedure uses purposive sampling based on predefined criteria, resulting in a sample of 55 companies. The dependent variable in this study is financial performance, while the independent variables are capital structure, liquidity, company size, and company age. The data analysis method uses panel data. The research results indicate that capital structure has a positive and significant effect on financial performance, liquidity has a positive and significant effect on financial performance, company size has a positive and significant effect on financial performance, and company age has a negative and significant effect on financial performance.